A Curious Case of Iron-Deficiency Anemia. (3rd April 2016) - Shaffer, Seth; Brahmania, Mayur; Shah, Hemant
Abstract : A 49-year-old Brazilian male presented to the emergency department with a five-day history of abdominal pain, dark stools, and syncope. Physical examination did not reveal any melena on digital rectal examination and there were no stigmata of chronic liver disease. Laboratory results showed hemoglobin of 47 g/L, MCV of 80 fL, and ferritin of 6 ng/mL. Liver enzymes and liver function tests were normal. Abdominal ultrasound showed a cirrhotic liver with splenomegaly and varices suggestive of portal hypertension. His past history was significant for cirrhosis based on a previous variceal bleed but a workup for chronic liver disease was negative and a liver biopsy did not show steatosis, fibrosis, or cirrhosis. A gastroscopy in this admission showed large esophageal varices without high-risk stigmata and no overt bleeding was seen. A colonoscopy was subsequently completed to the terminal ileum and was normal aside from a 5 mm sessile polyp in the descending colon.